Weathering the Storm : The Economies of Southeast Asia in the 1930s Depression - Boomgaard, Peter (Book collections on Project MUSE., 2001)
The principal cause of the 1930s depression in Southeast Asia lay outside the region -- through a sharp contraction in demand for the region's major commodity exports. But it had important internal causes too: an oversupply of primary commodities and an increasing scarcity of new agricultural land leading to higher rents and lower wages, rising indebtedness and increasing landlessness. This work thoroughly analyses the pre-war depression. It also looks at the changes in the basic structures of ...